Item Analysis of English Summative Test at The Eleventh Grade Students of SMA Negeri 9 Kota Jambi City Academic Year 2018/2019 - Ardhan Khariri; Suyadi Suyadi (Universitas Batanghari Jambi, 2020)
Summative test is method of evaluation performed at the end of a unit that allows a teacher to measure a student's understanding, typically against standardized criteria. Therefore, to measure students' comprehension of the material learned, the item analysis of summative test is necessary. The research is aimed to find out the level of English Summative Test items for the eleventh grade students of SMAN 9 Kota Jambi 2018/2019. This research is categorized as quantitative method. The researcher took one class XI IPA 1 which consisted 32 members of student. The total number of the test is 40 items. This research is supported by ANATES 4.0 and Manual Counting to analyze item test. Based on item analysis and discussion, the reseacher found that the difficult item was six items ( 15% ) with the test numbers are 3, 6, 8, 26, 27, 29. Secondly, medium item was nineteen items (47,5%) with the test numbers are 1, 4, 5, 7, 10, 11, 15, 20, 23, 25, 31, 32, 33, 34, 35, 37, 38, 39, 40. The last, the easy item was fifteen items ( 37,5%) with the test numbers are 2, 9, 12, 13, 14,16, 17, 18, 19, 21, 22, 24, 28, 30, 36. Most of the items were categorized as medium interpretation, and only a few in easy and difficult interpretation. It concluded that the total index level of the test is 0,59. Therefore, the summative test is categorized in medium level. The researcher concludes that the English summative test for eleventh grade at SMAN 9 Kota Jambi is not well enough yet and it has quite difficulties as well.Keywords: Item Analysis, English Summative Test.